The impact of the western liberal arts education in the MENA region: A case study - Mansour, Heba Abdelrahman Ibrahim (AUC Knowledge Fountain, 2018)
This study focuses on the development of the millennial generation within the liberal arts education setting. It has been demonstrated that the values of different generations periodically change. It is the university's duty to articulate the distinctive sociological, ideological, and psychological variations of each generation in order to provide the most viable educational system. Follow-up researches in different educational systems should be conducted regularly in order to incorporate new data from the rapidly changing millennial generation. This particular research focuses on understanding student development models that adequately demonstrate the effectiveness of a liberal arts education within the MENA region. The emphasis of this paper is on Arab students within transnational settings, focusing on the American University in Cairo and the American University of Kuwait.